MEMBANGUN INTERAKSI SOSIAL DENGAN PERMAINAN PADA SISWA BROKEN HOME DI SMK X KARANGANYAR - Rahmah, Hasna Rohadatul ‘Aisy; Calsum, Astri Yani; Zabba, Haningrum Rossa; Kristanto, Ichsan; Ruhaena, Lisnawati (PT. Naureen Digital Education, 2024)
One of the problems that occurs at SMK X Karanganyar in broken home students is the lack of social interaction. At SMK X, 40 students were identified who experienced broken homes and needed treatment to improve their social interaction skills. So community service was carried out in the form of activities in the form of eel catching games, odd even numbers, guessing words and clapping numbers. This activity was attended by 31 students with two sessions for giving pre tests and post tests. The results obtained an increase of 3.07 with a pre test of 42.58 and a post test of 45.65. The results of the t test showed p=0.001 <0.05 so that it showed a significant difference. So it is concluded that the game can improve the social interaction of students at SMK X Karanganyar.